Assessment of the Level of Trace Metals in Commonly Edible Vegetables and Fruits of Baghdad City (Iraq) - Salman, J.D.; Sulaiman, I.D.; Abd Al-Raziq, S.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A study was carried out to determine the concentrations of trace metals in vegetables and fruits, which are locally available in the markets of Baghdad-samples of fourteen varieties of vegetables and fruits, belonging to Beta vulgaris, Brassica rapa, Daucus carota, Allium cepa, Eurica sativa, Malva silvestris, Coriandrum Sativum, Trigonella Foenum craecum, Anethum graveolens, Barassica oleracea, Phaseolus vulgaris, citrus reticulata, Pyrus malus, and Punica granatum. Analysis for Cd,Pb, Mn, Fe, Co, Ni, Cu and Zn were determined by flame atomic absorption spectrophotometry. The results indicated that the Malva silvestris recorded the highest concentrations of Cd and Mn while Allium cepa showed the highest concentrations of Pb and Cu. But Eurica sativa, Anethum graveolens, phaseolus vulgaris and Daucus carota were observed the highest values of Fe, Co, Ni and Zn respectively. It can be noticed that the zinc has the highest values while the nickel recorded the lowest values in all studied samples.